Risk factors associated with the prevalence of thyroid nodules in adults in Northeast China: a cross-sectional population-based study - Zhen Zhang; Shufeng Li; Yudie Yan; Junhe Dong; Guochun Yang; Kunbo Huang; Wen Tian; Jingtong Su (BMJ Open, 2023)
Objectives This study examined the association between anthropometric measurements, lifestyle factors and the prevalence of thyroid nodules among adults in Northeast China.Design We employed a cross-sectional approach involving a questionnaire survey, which focused on participants’ living habits, and a physical examination that included anthropometry and ultrasound imaging.Setting The data were procured during multiple trips by medical teams from the first hospital of China Medical University to towns in Northeast China.Participants Of the 1092 participants, 489 did not have thyroid nodules (mean age: 54.02±11.49 years; 297 females (60.7%)), 99 had single thyroid nodules (mean age: 58.19±10.77 years; 59 females (59.6%)) and 504 had multiple thyroid nodules (mean age: 60.05±10.68 years; 394 females (78.2%)). Inclusion criteria mandated participants be over 20 years old without other medical conditions. We excluded individuals who had undergone surgical resection for thyroid nodules.Results The prevalence of thyroid nodules was significantly associated with being female (OR 2.569, 95% CI 1.937 to 3.405, p<0.001) and increased age (OR 1.054, 95% CI 1.041 to 1.066, p<0.001). This association was more pronounced in those with multiple thyroid nodules. For males under 60, non-smoking was inversely correlated with the prevalence of multiple thyroid nodules (OR 0.321, 95%CI 0.149 to 0.69, p<0.05). For females under 60, diastolic blood pressure (DBP) was significantly linked with the prevalence of thyroid nodules (OR 0.978, 95% CI 2.614 to 2.705, p<0.05).Conclusions Besides gender and age, the prevalence of thyroid nodules in Northeast China correlates with smoking habits and DBP.